2015
DOI: 10.1007/s00520-015-2817-3
|View full text |Cite
|
Sign up to set email alerts
|

Improving psychosocial outcomes for caregivers of people with poor prognosis gastrointestinal cancers: a randomized controlled trial (Family Connect)

Abstract: This standardized intervention did not demonstrate any significant improvements in caregiver well-being but did result in a decrease in patient emergency department presentations and unplanned hospital readmissions in the immediate post-discharge period. The trend towards improvements in a number of caregiver outcomes and the improvement in health service utilization support further development of telephone-based caregiver-focused supportive care interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(88 citation statements)
references
References 37 publications
1
86
0
1
Order By: Relevance
“…Five studies reported significant differences in Quality of Life aspects: three of them showed significant effects in all dimensions of Quality of Life [52,65,67]; Two studies showed significant effects in spiritual and social well-being [59,65], while one study [60] showed significant outcomes in social well-being. Emotional distress or stress symptoms revealed significant differences between pre-and post-treatment in five of the considered studies [50,52,65,67,69], while both depressive symptoms [55,57,65] and perceived social support [62,65,66] improved in three different trials. Furthermore, included articles reported significant effects -albeit smaller -in other measured outcomes: after the completion of the interventions, family members also experienced less anxiety, less sense of disruptiveness, hopelessness and uncertainty, less burden, and negative appraisal of caregiving.…”
Section: Measured Outcomesmentioning
confidence: 91%
See 4 more Smart Citations
“…Five studies reported significant differences in Quality of Life aspects: three of them showed significant effects in all dimensions of Quality of Life [52,65,67]; Two studies showed significant effects in spiritual and social well-being [59,65], while one study [60] showed significant outcomes in social well-being. Emotional distress or stress symptoms revealed significant differences between pre-and post-treatment in five of the considered studies [50,52,65,67,69], while both depressive symptoms [55,57,65] and perceived social support [62,65,66] improved in three different trials. Furthermore, included articles reported significant effects -albeit smaller -in other measured outcomes: after the completion of the interventions, family members also experienced less anxiety, less sense of disruptiveness, hopelessness and uncertainty, less burden, and negative appraisal of caregiving.…”
Section: Measured Outcomesmentioning
confidence: 91%
“…Most of the studies were conducted in the USA (see Table 1), except for three studies carried out in Australia [50,62], one in Sweden [63] and one in Canada [48]. …”
Section: Caregiver Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations